Nasal Decolonisation of MRSA - Peter Mantle (MDPI AG, 2019)
The recent demonstration for the first time of urinary monic acid A as a clinical urinary biomarker of exposure to intra-nasal mupirocin during medication for methicillin-resistant Staphylococcus aureus (MRSA) offers a way of verifying adherence to the regimen. However, absence of the biomarker in some patients needs explanation, to ensure that efficient decolonisation has not been compromised by confounding circumstances, and that additional resistance to mupirocin has not unwittingly been encouraged.